Videogames as a learning tool: is game-based learning more effective? (Revista Lusófona de Educação, 2018)
The potential of videogames in learning has been increasingly studied, documented and sustained. The present study aims to summarize quantitative results from digital Game-Based Learning (GBL) strategies, through a Systematic Review of Literature with Meta-analysis study, framing conclusions about the effectiveness of the use of videogames as a learning strategy in several contexts. Through a systematic search in scientific databases and researchers’ social networks (Ebsco, ACM, PubMed and ResearchGate), 68 papers were obtained. A screening process, based on inclusion criteria, such as the use of Randomized Controlled Trials (RCTs), digital GBL strategies and measures to evaluate concrete learning gains, resulted in a final sample of 14 experimental studies. Data was gathered and analyzed using two different matrices, and softwares (SPSS and CMA). Considering a joint sample of 1685 subjects, it is possible to mention that digital GBL strategies have shown larger effect-sizes than traditional approaches, namely expository, allowing larger and more effective learning outcomes. This study arises in the context of GamiLearning project, an action-research project, aiming to develop critical and participatory dimensions of media literacy in young people, from 9 to 12 years, through collaborative learning experiences with digital games.Keywords: meta-analysis; videogame-based learning; learning; education.